Developmental Shift of Inhibitory Transmitter Content at a Central Auditory Synapse - Nerlich, Jana (Front Cell Neurosci, 2017)
Synaptic inhibition in the CNS is mostly mediated by GABA or glycine. Generally, the use of the two transmitters is spatially segregated, but there are central synapses employing both, which allows for spatial and temporal variability of inhibitory mechanisms. Spherical bushy cells (SBCs) in the mammalian cochlear nucleus receive primary excitatory inputs through auditory nerve fibers arising from the organ of Corti and non-primary inhibition mediated by a dual glycine-GABA transmission. Slow kinetics IPSCs enable activity dependent tonic-like conductance build up, functioning as a gain control by filtering out small or temporally imprecise EPSPs. However, it remained elusive whether GABA and glycine are released as content of the same vesicle or from distinct presynaptic terminals. The developmental profile of quantal release was investigated with whole cell recordings of miniature inhibitory postsynaptic currents (mIPSCs) from P1–P25 SBCs of Mongolian gerbils. GABA is the initial transmitter eliciting slow-rising and -decaying events of relatively small amplitudes, occurring only during early postnatal life. Around and after hearing onset, the inhibitory quanta are predominantly containing glycine that—with maturity—triggers progressively larger and longer mIPSC. In addition, GABA corelease with glycine evokes mIPSCs of particularly large amplitudes consistently occurring across all ages, but with low probability. Together, these results suggest that GABA, as the primary transmitter released from immature inhibitory terminals, initially plays a developmental role. In maturity, GABA is contained in synaptic vesicles only in addition to glycine to increase the inhibitory potency, thereby fulfilling solely a modulatory function.